Fire Performance and Properties of Particleboards Made from Kenaf (Hibiscus Cannabinus L.) Core Treated with Fire Retardants - Kamal, Izran (2009)
A study was undertaken to evaluate the fire performance and properties of particleboard made from kenaf core treated with fire retardants. The specific objectives involved firstly, to determine the optimum concentrations of phosphorous-based fire retardants (monoammonium phosphate [MAP]), diammonium phosphate [DAP] and mixture of guanylurea phosphate, boric acid and phosphoric acid [BP®] for the treatment of kenaf particles; secondly, to determine the buffering capacity and gelation time of mixture of particles with fire retardants; and thirdly, to evaluate the adverse fire performance of kenaf particleboard fabricated from pre treated particles and to assess the physical and mechanical properties of the treated particleboard. Kenaf core particles with size 1-2 mm were first soaked in hot fire retardant solutions for ten min with two concentrations (8% and 10%). Kenaf particles that had been soaked in 10% concentration of DAP, MAP and BP® took 14, 15 and 36 min to achieve the standard chemical loading respectively. Longer soaking times were recorded for kenaf particles soaked in the same fire retardant solutions at 8% concentration. The cold soaking times recorded were 21, 36 and 48 min to achieve the standard chemical loading. This shows that the kenaf core particles absorbed the chemicals faster in 10% than in 8% concentration of fire retardant solutions. For buffering capacity, the untreated kenaf core, DAP-treated kenaf core, MAP-treated kenaf core and BP®-treated kenaf core at 10% concentration needed 39.3, 136, 162 and 169 ml of NaOH to achieve pH 11 and smaller amounts of H2SO4 were used to achieve pH 3 i.e. 4.00, 7.75, 9.6 and 14 ml respectively. Similar results were recorded for kenaf core untreated and treated with 8% fire retardants. The kenaf core, DAP-treated kenaf core, MAP-treated kenaf core and BP®-treated kenaf core at 8% concentration needed 39.3, 176, 103 and 156 ml of NaOH to achieve pH 11 and the smaller amounts of H2SO4 used to achieve pH 3 were 4.00, 17.5, 11.25 and 9 ml respectively. DAP-treated kenaf was found to have a lower buffering capacity towards alkali compared to other fire retardants for both concentrations. As for gelation time, the average times taken for 8% MAP-mixed resin and 8% DAP-mixed resins to cure were 28 and 150 s respectively. The pH values of these resins were 5, 8 and 6 respectively. The average times taken for 10% MAP- mixed resin, DAP-mixed resin and BP®-mixed resin to cure were 20, 160 and 101 s, with the pH values of the mixtures being 4, 9 and 6 respectively. As for the control sample, the average curing time was 140 s and the pH was neutral. Particleboards with density 700 kg/m3 from these treated kenaf core particles (10% concentration) were fabricated and their fire resistance, early burning and fire propagation performance were evaluated. Among the three phosphorous-based formulations, BP® showed the best performance in improving the insulation and integrity of kenaf particleboard. This was followed by MAP and DAP. BP®-treated board ignited least readily when compared with the rest of the boards. DAP and MAP were able to delay the maximum early heat release of the boards by about 15 to 16 min and 18 to 20 min respectively compared to BP® which was only able to delay the maximum early heat release by about 10 to 15 min after ignition. The heat release of the DAP and MAP-treated particleboards started 5 min after ignition, but the heat release of the BP®-treated boards started from the beginning of the test. It was shown that DAP-treated particleboards complied with the thickness swelling and water absorption requirements of the British-European standard. BP®-treated particleboards were found to have performance values better than the British-European standard requirement values for MOR and MOE. MAP-treated particleboards surpassed the standard requirement value for IB. All treated particleboards complied with the standard requirement of MOE except the DAP-treated particleboards. The untreated particleboards complied with all the standard requirements.